PERANAN OLAHRAGA BELADIRI MILITER YONGMOODO TERHADAP KEPERCAYAAN DIRI ANGGOTA TNI-AD - Triono, Sandi Dwi (STKIP Pasundan, 2019)
This study aims to determine whether the impact of Yongmoodo military martial sports on the self-confidence of TNI-AD members. The method used is the ex post facto method which is a research method used to solve or answer the problems faced in the current situation. The population in this study were members of the Indonesian Armed Forces in the Army Pangalengan. The sample used amounted to 27 people selected through simple random sampling technique. The instrument used was in the form of a questionnaire with the number of questions used 35 questions with instrument reliability 0.893. The results of the test of significance level indicate that the value of Sig. (2-tailed) of 0,000 smaller than <0.05, which means that there is a significant influence of Yongmoodo martial arts on the confidence of members of the Army. The results of processing the confidence percentage data were 91.78%, with sub-variables of confidence in self-ability 92.59%, optimistic 82.96%, objective 90.33%, and responsible 91.85%, rational and realistic 89, 38%. The conclusion of this study is that there is a significant influence on the yongmoodo military martial arts against the confidence of members of the TNI-AD SECATA, Pangalengan.